Hydraulic Research for Spillway Dam of Grodno Hydroelectric Station - G. G. Kruglov; N. N. Linkevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2009)
The paper describes hydraulic tests of discharge capacity and pool conjunction in respect of dam spillway of the Grodno hydroelectric station. The process of ice passage through the spillway dam has been studied in the paper. The paper contains recommendations on safety depth downstream.